Mind the gap: mechanisms regulating the endothelial barrier. (22nd March 2017) - Radeva, M. Y.; Waschke, J.
Abstract: The endothelial barrier consists of intercellular contacts localized in the cleft between endothelial cells, which is covered by the glycocalyx in a sievelike manner. Both types of barrier‐forming junctions, i.e. the adherens junction (AJ) serving mechanical anchorage and mechanotransduction and the tight junction (TJ) sealing the intercellular space to limit paracellular permeability, are tethered to the actin cytoskeleton. Under resting conditions, the endothelium thereby builds a selective layer controlling the exchange of fluid and solutes with the surrounding tissue. However, in the situation of an inflammatory response such as in anaphylaxis or sepsis intercellular contacts disintegrate in post‐capillary venules leading to intercellular gap formation. The resulting oedema can cause shock and multi‐organ failure. Therefore, maintenance as well as coordinated opening and closure of interendothelial junctions is tightly regulated. The two principle underlying mechanisms comprise spatiotemporal activity control of the small GTPases Rac1 and RhoA and the balance of the phosphorylation state of AJ proteins. In the resting state, junctional Rac1 and RhoA activity is enhanced by junctional components, actin‐binding proteins, cAMP signalling and extracellular cues such as sphingosine‐1‐phosphate (S1P) and angiopoietin‐1 (Ang‐1). In addition, phosphorylation of AJ components is prevented by junction‐associated phosphatases including vascular endothelial protein tyrosine phosphatase (VE‐PTP). In contrast, inflammatory mediators inhibiting cAMP/Rac1 signalling cause strong activation of RhoA and induce AJ phosphorylation finally leading to endocytosis and cleavage of VE‐cadherin. This results in dissolution of TJs the outcome of which is endothelial barrier breakdown.